Pengembangan Mikrokontroler ESP-32 Sebagai Alat Akusisi Data Untuk Monitoring Kinerja Sistem Refrigerasi Pada Laboratorium Teknik Refrigerasi dan Tata Udara - Sunardi, Sunardi; Nuriyadi, Muhammad (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Training units in refrigeration laboratories still use manual measurements. Manual data collection is very dependent on human observation, where the accuracy and time of data collection is unstable and the level of accuracy is low. For this reason, it is necessary to develop a data acquisition tool using an ESP-32 microcontroller as a data processor equipped with a DS18B20 temperature sensor, SCT013 electric current sensor and ZMPT101B voltage sensor. The development of this tool produces an output in the form of a monitoring tool that is able to store measurement data in real time and accurately for learning activities. From the analysis results, it was found that measuring air conditioning system parameters using Data Acquisition (DAQ ESP-32) produces dynamic measurements, more accurate and precise than manual measurements. The difference in parameters ranges from 4 to 10 percent. Keywords: Esp32; Data Logger; Measuring Instrument; Data Acquisition